The will to believe : novelists of the nineteen-thirties - Johnstone, Richard (Oxford University Press, 1982)
"A study of six novelists of the nineteen-thirties : Edward Upward, Rex Warner, Graham Greene, Evelyn Waugh, Christopher Isherwood, and George Orwell."--Pref.